Lesbian Rule Cultural Criticism and the Value of Desire - Villarejo, Amy (Book collections on Project MUSE., 2003)
Investigating what allows viewers to perceive an image or narrative as 'lesbian', Amy Villarejo presents a theoretical exploration of lesbian visibility.